An effective performance management system for a selected company in the construction industry - Vigaro, Magdelane Rosaline (Cape Peninsula University of Technology, 2013)
This paper aims to determine if there is a relationship between performance management and organisational performance owing to a lack of staff motivation. If there is such a relationship the paper aims to investigate implementation of performance management for a selected company in the construction industry. The paper begins by outlining the background and history of the construction industry and presents a review of literature of performance management which provides insight into the topic. The paper examined different views of performance management from both practitioners and organisations and discusses the aims, benefits and shortcomings of performance management. Additionally, different evaluation methods and performance measurement methods were investigated to provide an in-depth understanding of the topic. The background and overview of the selected company in the construction industry was discussed. The paper used a case study and qualitative research approach. The results of the research prove that there is an inverse relationship between performance management and the lack of motivation that affects organisational performance. The paper concludes by showing that the selected company is in need of a performance management system and suggesting the development of a performance management system that should support a culture, which is based on feedback and communication. A framework is presented which ensures that effective strategies are deployed to adopt a performance management system.
Thesis (MTech (Human Resource Management))--Cape Peninsula University of Technology, 2013
Keywords: Employees -- Rating of; Performance -- Management; Work measurement; Construction industry; Dissertations, Academic; MTech